Operational Characteristics of Immobilized Ochrobactrum sp. CUST210-1 Biosystem and Immobilized Chromate Reductase Biosystem in Continuously Treating Actual Chromium-Containing Wastewater - Guey-Horng Wang (Applied Sciences, 2020)
Cr(VI) detoxification by biotreatment is considered one of the most practical detoxification methods, especially at low-to-medium concentrations. Although the capabilities of chromium-reducing bacteria and related enzymes in removing Cr(VI) have been explored, little is known about their differences in engineering applications. In this study, Ochrobactrum sp. CUST210-1 was isolated and its chromate reductase identified and separated as biological elements in biosystems developed for Cr(VI) removal. Results indicate that intracellular Cr(OH)3(s) accounted for 88.01% of Cr(VI) reduction product, and a possible reduction mechanism was exposed. The chromate reductase in Ochrobactrum sp. CUST210-1 was ChrR protein, and its crystal structure was revealed. The toxicity of Cr(VI)-containing wastewater was decreased by 57.8% and 67.0% (at minimum) by the CUST210-1 strain and ChrR, respectively. The Ochrobactrum sp. CUST210-1 biosystem demonstrated good adaptability to pH (7–9), and the ChrR biosystem exhibited high removal efficiency (>98.2%) at a wide range of temperatures (25 °C–40 °C). The outlet Cr(VI) concentration of the CUST210-1 biosystem met the industrial discharge limit of 0.5 mg L−1 when the inlet Cr(VI) concentration in the actual Cr(VI)-containing wastewater was <430 mg L−1. The stricter water quality standard of 0.05 mg L−1 could be complied with by the immobilized ChrR biosystem when <150 mg L−1 Cr(VI) concentration was introduced. These developed biosystems can be used in the bioremediation of various Cr(VI)-contaminated wastewaters. Regarding capital costs, those of the CUST210-1 biosystem were higher. To our knowledge, this is the first report comparing differences in the economic and operational characteristics of bacteria and enzyme biosystems for Cr(VI) removal.